Estudo das propriedades elétricas de compósitos carbono-argila obtidos a partir da borra de petróleo pelo método de quatro pontas - Sousa, Makcydra Amisterdania Costa Ferreira (2010)
The petroleum industry produces significant amounts of residues in several of its processes, from the perforation of wells, production, storage, transport and refining, to the distribution of its derivatives. The wastewater generated in the oil extraction step is known as produced water and, when stored in flotation tanks, if generates a residue called oily sludge . In a previous report, carbon-clay composites were obtained from this oily sludge and it was found this the material shows semiconductor properties. Thus, here we aimed to further evaluate the electrical properties of the carbon-clay composites using a home-made four probe apparatus. The carbon-clay composites have been prepared using the pyrolysis conditions reported in the previous study, changing here the precursor granulometry then afterwards characterizing the samples by FTIR, XRD, Raman and SEM. The presence of clays-mineral phases as well as carbon rich phases was evidenced from FTIR spectroscopy. Raman spectra revealed the presence of graphitic crystallites in addition to a disordered carbon matrix. XRD data allowed us to properly identify the mineral phases. SEM images have shown a clear effect of the precursor granulometry on the microstructure of the final pellets. Compact pellets can be expected when using a precursor with smaller particle size. The electrical measurements were accomplished using both a current source especially built for this and alternatively a Keithey 237 electrometer coupled to the four-probe apparatus. Satisfactory current values in terms of stability and reproducibility were obtained with both sources in the range of 640 μA (minimum potential) 37 mA (maximum potential). Applying current values in this range for the carbon-clay composite samples it was possible to confirm their semiconductive properties, since conductivities were found to lie in the range ≈10-4 (Ω*cm)-1. Finally the sample compactness was found to play a significant role in the electrical conductivity since the higher conductivity values were found for more compact samples.